Ultrastructural pathology of primary ciliary dyskinesia: report about 125 cases in Germany - Theegarten Dirk; Ebsen Michael (BMC, 2011)
Abstract Background Primary ciliary dyskinesia (PCD) is a rare genetically induced disorder of cilia inducing mainly respiratory diseases. Transmission electron microscopy (TEM) analysis of ciliary ultrastructure is classically used for diagnosis. We report our experience of TEM investigations in a large series of patients. Methods TEM analysis performed of 742 biopsies from patients with suspected PCD was reviewed retrospectively. Ultrastructural defects were analysized further in 125 cases with changes typical for PCD. Results In 18.1% of patients diagnosis of PCD was made because of morphological alterations, in 68.2% secondary changes were seen. In 13.7% material was not feasible for analysis. Mostly defects of dynein arms were detected in PCD (96.8%). In particular defects of the inner arms (51.2%) and combined dynein defects (37.6%) were found. Total loss of dynein arms was dominant. Only in 3.2% deficiencies of central structures were found alone. Associated situs inversus or dextracardia was reported clinically in 21.4%. Conclusions TEM analysis is possible in most patients and a useful tool for diagnosis of PCD. Functional and genetic analysis should be done additionally. Registers should be installed to collect all available informations and push further research.